Broad Ligament Hematoma Following Vaginal Delivery –A Rare Entity - Bhansakarya, Rakina; Subedi, Shanti (Journal of Nobel Medical College, 2019)
Pelvic hematomas are common occurring in delivering the baby but spontaneous broad ligament hematoma following vaginal delivery is rarely seen and less than 100 cases are reported in literature. This article reports a rare case of broad ligament hematoma following vacuum delivery in 22 years Para1 lady with history of postpartum collapse 3 hours after delivery.